The Effect Of Quality Of Document Service To Customer Satisfaction In PT. Mediterranean Shipping - agus leonard; Imam Fachruddin; Deffan Ezra (Meteor STIP Marunda, 2020)
Mediterranean Shipping Company, is one of the major multinational companies in Indonesia, multinational companies can communicate with customers and sell to customers abroad without the need for a lot of physical investment in foreign markets (United Nations Conference On Trade, UNCTAD, 2017), through its market reach so large and with business relationships that are spread everywhere, then this company has a pretty good rating in the international business arena. PT. Mediterranean Shipping Company Indonesia develops its business as a shipping company in the field of International container transportation (export import) and offers various facilities for export to exporters.